Mapping the new left antisemitism
1 online resource.
Keywords: "Mapping the New Left Antisemitism: The Fathom Essays provides a comprehensive guide to contemporary Left antisemitism. The rise of a new and largely left-wing form of antisemitism in the era of the Jewish state, and the distinction between it and legitimate criticism of Israel is now roiling progressive politics in the West and causing alarming spikes in antisemitic incitement and incidents. Fathom Journal has examined these questions relentlessly in the first decade of its existence, earning a reputation for careful textual analysis and cogent advocacy. In this book, the Fathom essays are contextualised by three new contributions: Lesley Klaff provides a map of contemporary antisemitic forms of antizionism, Dave Rich writes on the oft-neglected lived experience of the Jewish victims of contemporary antisemitism, and David Hirsh assesses the intellectual history of the left from which both Fathom and his own London Centre for the Study of Contemporary Antisemitism, as well as this book series, have emerged. Topics covered by the contributors include: antisemitic anti-Zionism and its under-appreciated Soviet roots; the impact of analogies with the Nazis; the rise of antisemitism on the European continent, exploring the hybrid forms emerging from a cross-fertilisation between new left, Christian, and Islamist antisemitism; the impact of anti-Zionist activism on higher education; and the bitter debates over the adoption of the oft-misrepresented International Holocaust Remembrance Alliance (IHRA) definition of antisemitism. This work will be of considerable appeal to scholars and activists with an interest in antisemitism, Jewish studies, and the politics of Israel"--